The Centennial Edition of the 1908 Alpenverein Map of the Brenta Massif, Italy - Buchroithner, Manfred F.; Himpel, Thomas (ERDKUNDE, 2010)
The synergetic use of different traditional and, above all, modern techniques and technologies permitted the time-efficient production of a Centennial Edition of the world-famous high-mountain map of the Brenta Massif, first published in 1908. During the updating field survey in this extreme alpine terrain, classical cartographic field-sketching, terrestrial laser scanning, and geotagged landscape (stereo) photographing, together with measurements by geodetic and handheld GPS, were applied. Satellite imagery and digital image processing supported the digital cartographic work. However, glacier retreat areas had to be complemented by classical manual rock and scree drawing in the unique style of Aegerter-Rohn in order to maintain a homogeneous appearance of the re-used terrain depiction of the first edition.